PENDAMPINGAN SEKOLAH PERCONTOHAN DIGITAL MELALUI APLIKASI (I-SEKOLAHKU) DI SMA NEGERI 1 KABUPATEN BENGKULU TENGAH, BENGKULU - Susanto, Edi; Putri, Tiara Eka; Stiadi, Elwan (Jurnal Abdi Insani, 2024)
Technology to support learning activities in schools is essential to implement to improve learning outcomes. Technology use also aligns with the objectives of implementing an independent curriculum, which requires digital skills. However, the conditions in schools still need to be improved regarding the use of technology both in delivering learning material and in digital-based evaluations. Every school is required to participate in a national evaluation in the form of a computer-based minimum competency assessment (AKM), carried out online. This activity aims to increase the use of digital technology in schools, including administration, teaching, and learning at SMA Negeri 1 Bengkulu Tengah. Digital utilization is carried out through the use of the i-school application. The activity implementation method consists of (1) preparation and needs analysis, (2) application system design, (3) outreach, (4) implementation of training and use of technology, (5) evaluation and monitoring. The target of the training activities consisted of 30 teachers and staff and 36 students. The result of this activity is creating a digital application to support administration, teaching, and learning activities that can be implemented in the target school. This activity also impacts increasing the teacher's ability to use open materials and online test tools through the i-school application. Students' responses to application usage activities are also at high criteria. Based on the activities carried out, it can be concluded that the use of technology through the i-school application can get a good response from the target of the activity and can be used in other schools.